Carbon Dioxide Adsorption-Induced Deformation of Microporous Carbons - Kowalczyk, Piotr; Furmaniak, S.; Gauden, P.; Terzyk, A. (American Chemical Society, 2010)
Applying the thermodynamic model of adsorption-induced deformation of microporous carbons developed recently (Kowalczyk, P.; Ciach, A.; Neimark, A. Langmuir 2008, 24, 6603), we study the deformation of carbonaceous amorphous porous materials due to adsorption of carbon dioxide at 333 K and pressures up to 27 MPa. The internal adsorption stress induced by adsorbed/compressed carbon dioxide is very high in the smallest ultramicropores (for instance, solvation pressure in 0.23 nm ultramicropore reaches 3.2 GPa at 27 MPa). Model calculations show that any sample of carbonaceous porous solid containing a fraction of the smallest ultramicropores with pore size below 0.31 nm will expand at studied operating conditions. This is because the high internal adsorption stress in ultramicropores dominates sample deformation upon adsorption of carbon dioxide at studied operation conditions. Interestingly, the nonmonotonic deformation (i.e., initial contraction and further expansion) of the above mentioned porous materials upon adsorption of carbon dioxide at 333 K is also theoretically predicted. Our calculations reproduce quantitatively the strain isotherm of carbon dioxide on carbide-derived activated carbon at 333 K and experimental pressures up to 2.9 MPa. Moreover, we extrapolate adsorption and strain isotherms measured by the gravimetric/dilatometric method up to 27 MPa to mimic geosequestration operating conditions. And so, we predict that expansion of the studied carbon sample reaches 0.75% at 27 MPa and 333 K. Presented simulation results can be useful for the interpretation of the coal deformation upon sequestration of carbon dioxide at high pressures and temperatures.